Fibrosis and other histological features in chronic hepatitis C virus infection: a statistical model. Issue 6 (June 1996) - Wong, V S; Wight, D G; Palmer, C R; Alexander, G J
Abstract : AIMS: To study the inter-relation between hepatic fibrosis and other histological features of chronic hepatitis C virus (HCV) infection. METHODS: Liver biopsy specimens from 200 consecutive patients with chronic HCV infection were graded and staged separately for necro-inflammatory activity and for fibrosis. The interaction between fibrosis and other histological features was evaluated by univariate and multivariate analysis, followed by hierarchical log linear modelling. RESULTS: The most striking feature was the presence of portal tract inflammation in 177 (89%) of 200 samples. Lymphoid aggregates/follicles were observed either alone or as part of the general inflammatory infiltration of the portal tracts in 120 (60%) of 200 samples. Fatty change (macro- and microvesicular steatosis) was observed in 76 (38%) samples: mild to moderate in 60 (30%) and diffuse in 16 (8%). Bile duct damage was found in 30 (15%) of 200 specimens. Lobular activity was found in 154 (77%) of 200 samples and was significant in 44; piecemeal necrosis was present in 79 (40%). Thirty one (16%) patients had stage 0 liver fibrosis, 27 (14%) had stage 1, 69 (35%) had stage 2, 43 (22%) had stage 3, 16 (8%) had stage 4, and 12 (6%) had stage 5. On log linear analysis, piecemeal necrosis, lobular inflammation and steatosis were linked directly with fibrosis. Portal tract inflammation was linked directly and indirectly via piecemeal necrosis and lobular inflammation with fibrosis. The presence of lymphoid aggregates was associated with bile duct damage. CONCLUSIONS: Portal tract inflammation with lymphoid aggregates or follicles, together with fatty change, bile duct damage and/or lobular activity, are characteristic of chronic HCV infection, confirming previous reports. Piecemeal necrosis, lobular inflammation, portal inflammation, and steatosis are linked directly with fibrosis in this statistical model, suggesting a close inter-relation in the development of fibrosis/cirrhosis.